REVIEW OF HISTORICAL DEVELOPMENT IN THE ALBANIAN CRIMINAL CODE OF THE NARCOTIC PROBLEMS - Qafa, Fran (European Scientific Journal, ESJ, 2013)
The purpose of this paper is the presentation and the legal comparison of offenses of narcotics and the approach in time under the Albanian Criminal Code. In the early 90 Albania changed its economic and political system. Our country was opened to the western countries undertaking reforms in each field to build a free and democratic society. Except the positive sides these changes were accompanied also with some negative, antisocial phenomena as the drug, the prostitution, different illegal traffics etc. Due to the high social risk of this phenomena raised the necessity of their fighting with all the possible tools. One of these tools are also the judicial-penal measures. The Criminal Code of Zog inspired by the Western Criminal Codes, certainly made a very good adjustment for the time and the conditions in which this Code emerged. Also to help the justice and in order to not allow the avoidance by the criminal sentence of the persons who performed such activities and who were related to the drug at this time was signed also the Treaty of extradition between the United States of America and the Albanian Kingdom. The later Criminal Codes as the one of 1952 and 1977 made again a legal adjustment of the drug offenses in a provision, a regulation that was very restricted compared with the one of Zog, but that was probably such because the political situation was the same where the control was very powerful and as shown by the judicial practice few or no person was convicted for this offence. The further developments, as for the other offences, brought the necessity of a more complete and accurate legal regulation. These regulations were made with the Criminal Code of 1995. The paper will focus on these issues: The theoretical development of the Albanian Criminal Code in relation to the offences of narcotics. Suggestions for the improvement of the legal framework in relation to the fight against the offences of narcotics.